Enhancement of Anodically Treated Stainless Steel by NiFeP-Catalyst Electrodeposition as Bifunctional Electrodes for Water Electrolysis - Cartagena, Santiago; Bedoya-Lora, Franky E.; Calderón, Jorge A. (Journal of the Electrochemical Society, 2022)
Electrochemical water splitting, using bifunctional and easily scalable electrodes made of abundant materials, is one of the most important milestones towards the storage of intermittent energy generated from renewable sources. In this work, we demonstrated the synthesis of amorphous NiFeP catalysts for H 2 and O 2 evolution using a very simple and scalable electrodeposition method. Corrosion resistant stainless steel was used as substrate, which is subject of improvement by a facile anodic treatment in an electrolyte comprised of sulfuric acid and glycerol. This treatment increased the surface area approx. six-fold by dissolving parts of the stainless steel substrate. Electrodes with NiFeP catalyst supported on pretreated substrates reported overpotentials of 305 and 210 mV at ∣10∣ mA cm −2 for oxygen evolution reaction (OER) and hydrogen evolution reaction (HER), respectively. The electrodes were stable for 24 h at a current density of 400 mA cm −2 , which resembles real operation for alkaline electrolyzers, with a slight increase in the overpotentials due to the accumulation of bubbles at the surface.